Method for treating sand aggregate production wastewater of hydropower station

By using zeolite flocculant that is wrapped with adsorption film prepared by wrapping quartz nanoparticles and binder on the surface of the zeolite, the problems of poor purification effect of the production wastewater of sand and gravel aggregates in hydropower stations and large residual amount of flocculant are solved, and efficient purification and zero emissions are achieved.

CN119873992APending Publication Date: 2025-04-25SINOHYDRO BUREAU 5
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510062334.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The purification effect of the wastewater for sand and gravel aggregate production in hydropower stations is poor, and the remaining amount of flocculant added is large, which affects the performance of concrete.

Method used

A zeolite flocculant prepared from silicon source, tetrabutyl ammonium hydroxide, dodecyl trimethyl ammonium chloride and water is used. The flocculant is wrapped with an adsorption film prepared by quartz nanoparticles and a binder on the surface of the zeolite to form a mesoporous 30nm to 50nm, which improves the adsorption capacity of the flocculant.

Benefits of technology

It has achieved efficient purification of wastewater from sand and gravel aggregate production in hydropower stations, reduced the residual amount of flocculant, ensured the stability of concrete performance, and achieved zero discharge of wastewater.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a treatment method of hydropower station sandstone aggregate production wastewater, and relates to the technical field of wastewater treatment.The method comprises the steps that the hydropower station sandstone aggregate production wastewater is introduced into a sedimentation tank, and a flocculating agent is added into the sedimentation tank to conduct sedimentation treatment on the wastewater; when the SS concentration in the supernatant of the sedimentation tank is less than 100mg / L, introducing the supernatant into a clear water tank, and introducing water in the clear water tank into a gravel processing system for recycling; the flocculant is zeolite prepared from a silicon source, tetrabutyl ammonium hydroxide, dodecyl trimethyl ammonium chloride and water, the surface of the zeolite is coated with an adsorption film, and 30-50 nm mesopores are formed in the surface of the zeolite; the adsorption film is prepared from quartz nanoparticles and a binder. By adding the flocculating agent, the effect of purifying the sand aggregate production wastewater of the hydropower station can be achieved, and the residual amount of the added flocculating agent in the wastewater is small.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wastewater treatment, and in particular to a method for treating wastewater from sand and gravel aggregate production in a hydropower station. Background Art

[0002] At present, the domestic water environment governance situation is severe. From the perspective of social sustainable development, water environment protection and governance are the basis for promoting social sustainable development. As a national key project, Xulong Hydropower Station is located in Ganzi Tibetan Autonomous Region, Sichuan and Diqing Tibetan Autonomous Region, Yunnan, and is located in the upper reaches of the Jinsha River. Water environment protection and governance is one of its key tasks, and the treatment and reuse of production wastewater is an important link and measure for water environment protection and governance. During the construction period of Xulong Hydropower Station, research on the treatment and reuse of production wastewater will provide advanced production wastewater treatment technology for similar domestic and foreign water conservancy and hydropower projects, and reduce the cost of production wastewater treatment, which has long-term value and important significance.

[0003] The Xulong low-line sand and gravel processing system is located on the Yunnan side of the upper reaches of the Jinsha River. It has a designed finished product production capacity of 240t. It is the largest source of wastewater generated during the construction period of the Xulong Hydropower Project, accounting for more than 70% of the wastewater generated during the construction period. In accordance with the national concept of building environmental protection projects and responding to the owner's environmental and water protection management system requirements, production wastewater must achieve "zero discharge" and be fully treated and reused.

[0004] The source of the sand and gravel processing system of Xulong Hydropower Project is granite. The lime powder content in the production wastewater is high, which can reach more than 100,000 mg / L. At the same time, it is extremely difficult to settle due to its particle size. The construction land of Xulong Hydropower Project is tight, and it is not possible to treat the wastewater by building a large sedimentation tank and using a completely natural sedimentation method. At the same time, the treatment method of adding flocculants for sedimentation has the risk of affecting the performance of concrete due to the residue of flocculants in the wastewater. Summary of the invention

[0005] In view of the problem that the existing hydropower station sand and gravel aggregate production wastewater purification effect is poor, the purpose of the present invention is to provide a method for treating hydropower station sand and gravel aggregate production wastewater. By adding the flocculant in the present application, not only can the hydropower station sand and gravel aggregate production wastewater purification effect be achieved, but also the residual amount of the added flocculant in the wastewater is also small.

[0006] The present invention is achieved through the following technical solutions:

[0007] The present application provides a method for treating wastewater from sand and gravel aggregate production in a hydropower station, comprising the following steps:

[0008] The wastewater from the production of sand and gravel aggregates in the hydropower station is passed into the sedimentation tank, and flocculants are added to the sedimentation tank to precipitate the wastewater;

[0009] When the SS concentration in the supernatant of the sedimentation tank is less than 100 mg / L, the supernatant is passed into the clear water tank, and then the water in the clear water tank is passed into the sand and gravel processing system for reuse;

[0010] The flocculant is a zeolite prepared from a silicon source, tetrabutylammonium hydroxide, dodecyltrimethylammonium chloride and water. The surface of the zeolite is coated with an adsorption film, and mesopores of 30nm to 50nm are formed on the surface of the zeolite. The adsorption film is prepared from quartz nanoparticles and a binder.

[0011] The flocculant added in the present application adopts a structure in which a layer of adsorption film is wrapped on the surface of zeolite, which improves the adsorption capacity of the flocculant. In particular, the adsorption film prepared by the quartz nanoparticles and the binder in the present invention has a good treatment effect on the stone powder in the production wastewater. On the one hand, the quartz nanoparticles can adsorb the lime powder in the wastewater on its surface. On the other hand, the lime powder adsorbed on the surface of the quartz nanoparticles will also react with the quartz nanoparticles to generate crystals with high crystal structure strength and good stability. In addition, there are mesopores on the surface of the formed crystals, which can adsorb other wastes in the wastewater, thereby further achieving the purification effect of the wastewater. Therefore, the adsorption film prepared by using this material can not only remove the stone powder in the wastewater, but also adsorb other wastes, achieving the effect of one thing with two effects.

[0012] In addition, the dodecyltrimethylammonium chloride added to the raw materials for preparing zeolite in the present application not only acts as a surfactant when generating zeolite to promote the co-condensation reaction of the silicon source, but also deprotonates the hydroxyl groups on the surface of the quartz nanoparticles in the adsorption film to form silane alcohol salts, which then interact with the ammonium ions in the dodecyltrimethylammonium chloride, making the adsorption film more stably wrapped on the surface of the zeolite.

[0013] Furthermore, the mass ratio of the silicon source, tetrabutylammonium hydroxide, dodecyltrimethylammonium chloride and water is 1:(0.02-0.08):(0.2-0.3):(50-150).

[0014] Furthermore, the silicon source includes methyl orthosilicate, propyl orthosilicate or silica sol.

[0015] Furthermore, the binder includes polyethylene or polypropylene.

[0016] Furthermore, the mass ratio of the quartz nanoparticles to the binder is 1:(0.3-0.6).

[0017] Furthermore, the preparation method of the zeolite comprises the following steps:

[0018] The silicon source and water are mixed evenly, and the pH value is adjusted to 10-11, and then tetrabutylammonium hydroxide and dodecyltrimethylammonium chloride are added dropwise, and stirred to react to obtain a silicate gel;

[0019] The silicate gel is crystallized, and then the crystallized product is calcined at a temperature of 530° C. to 560° C. to obtain zeolite.

[0020] Furthermore, the crystallization temperature is 75° C. to 85° C., and the crystallization time is 90 h to 100 h.

[0021] Furthermore, the preparation method of the adsorption film comprises the following steps:

[0022] Adding quartz nanoparticles into water, stirring and mixing, and preparing a suspension;

[0023] Adding a binder into the suspension and stirring to mix well to obtain a membrane liquid;

[0024] The prepared membrane liquid is deposited on zeolite to form an adsorption membrane.

[0025] Furthermore, the deposition method includes vacuum filtration, dip coating or suspension coating.

[0026] Furthermore, the mass ratio of the quartz nanoparticles to water is 1:(100-120).

[0027] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0028] (1) The flocculant added in the present application adopts a structure in which a layer of adsorption film is wrapped on the surface of zeolite, thereby improving the adsorption capacity of the flocculant. In particular, the adsorption film prepared by the quartz nanoparticles and the binder in the present invention has a good treatment effect on the stone powder in the production wastewater. On the one hand, the quartz nanoparticles can adsorb the lime powder in the wastewater on its surface. On the other hand, the lime powder adsorbed on the surface of the quartz nanoparticles will also react with the quartz nanoparticles to generate crystals with high crystal structure strength and good stability. In addition, there are mesopores on the surface of the formed crystals, which can adsorb other wastes in the wastewater, thereby further achieving the purification effect of the wastewater. Therefore, the adsorption film prepared by using this material can not only remove the stone powder in the wastewater, but also adsorb other wastes, thus achieving a two-effect effect.

[0029] (2) The dodecyltrimethylammonium chloride added to the raw materials for preparing zeolite in the present application not only acts as a surfactant to promote the co-condensation reaction of the silicon source when generating zeolite, but also deprotonates the hydroxyl groups on the surface of the quartz nanoparticles in the adsorption film to form silane alcohol salts, which then interact with the ammonium ions in the dodecyltrimethylammonium chloride, making the adsorption film more stably wrapped on the surface of the zeolite. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0031] The "range" disclosed in this application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range.

[0032] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0033] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0034] If there is no special explanation, all the steps of the present application can be performed sequentially or randomly, preferably sequentially.

[0035] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0036] Example 1

[0037] This embodiment provides a method for treating wastewater from sand and gravel aggregate production in a hydropower station, which is carried out by the following steps:

[0038] S1. The wastewater from the production of sand and gravel aggregates in the hydropower station is passed into a sedimentation tank, and flocculants are added into the sedimentation tank to perform sedimentation treatment on the wastewater;

[0039] The flocculant is a zeolite prepared from a silicon source, tetrabutylammonium hydroxide, dodecyltrimethylammonium chloride and water, and the mass ratio of methyl orthosilicate, tetrabutylammonium hydroxide, dodecyltrimethylammonium chloride and water is 1:0.05:0.25:100; the surface of the zeolite is coated with an adsorption film, and 40nm mesopores are formed on the surface of the zeolite; the adsorption film is prepared from quartz nanoparticles and polyethylene; the mass ratio of quartz nanoparticles to polyethylene is 1:0.5.

[0040] Wherein, the preparation method of flocculant is:

[0041] S1-1. Evenly mix methyl orthosilicate and water, and adjust the pH value to 10. Then, add tetrabutylammonium hydroxide and dodecyltrimethylammonium chloride dropwise, and stir to react to obtain silicate gel.

[0042] S1-2. Crystallize the silicate gel at a temperature of 80° C. for 95 hours, and then calcine the crystallized product at a temperature of 550° C. to obtain zeolite.

[0043] S1-3. Add quartz nanoparticles into water, stir and mix to prepare a suspension; the mass ratio of quartz nanoparticles to water is 1:110.

[0044] S1-4, adding polyethylene into the suspension and stirring to mix well to obtain a membrane liquid.

[0045] S1-5. The prepared membrane liquid is deposited on the zeolite by dip coating to form an adsorption film, thereby obtaining a zeolite flocculant with 40 nm mesopores on the surface.

[0046] S2. When the SS concentration in the supernatant of the sedimentation tank is less than 100 mg / L, the supernatant is passed into the clear water tank, and then the water in the clear water tank is passed into the sand and gravel processing system for reuse.

[0047] Example 2

[0048] This embodiment provides a method for treating wastewater produced by sand and gravel aggregate production in a hydropower station. The difference from Embodiment 1 is that the dosage ratios of the raw material components for preparing zeolite in this embodiment are different, specifically: the mass ratio of methyl orthosilicate, tetrabutylammonium hydroxide, dodecyltrimethylammonium chloride, and water is 1:0.02:0.2:50.

[0049] The following steps are used:

[0050] S1. The wastewater from the production of sand and gravel aggregates in the hydropower station is passed into a sedimentation tank, and flocculants are added into the sedimentation tank to perform sedimentation treatment on the wastewater;

[0051] The flocculant is a zeolite prepared from a silicon source, tetrabutylammonium hydroxide, dodecyltrimethylammonium chloride and water, and the mass ratio of methyl orthosilicate, tetrabutylammonium hydroxide, dodecyltrimethylammonium chloride and water is 1:0.02:0.2:50; the surface of the zeolite is coated with an adsorption film, and 40nm mesopores are formed on the surface of the zeolite; the adsorption film is prepared from quartz nanoparticles and polyethylene; the mass ratio of quartz nanoparticles to polyethylene is 1:0.5.

[0052] Wherein, the preparation method of flocculant is:

[0053] S1-1. Evenly mix methyl orthosilicate and water, and adjust the pH value to 10. Then, add tetrabutylammonium hydroxide and dodecyltrimethylammonium chloride dropwise, and stir to react to obtain silicate gel.

[0054] S1-2. Crystallize the silicate gel at a temperature of 80° C. for 95 hours, and then calcine the crystallized product at a temperature of 550° C. to obtain zeolite.

[0055] S1-3. Add quartz nanoparticles into water, stir and mix to prepare a suspension; the mass ratio of quartz nanoparticles to water is 1:110.

[0056] S1-4, adding polyethylene into the suspension and stirring to mix well to obtain a membrane liquid.

[0057] S1-5. The prepared membrane liquid is deposited on the zeolite by dip coating to form an adsorption film, thereby obtaining a zeolite flocculant with 40 nm mesopores on the surface.

[0058] S2. When the SS concentration in the supernatant of the sedimentation tank is less than 100 mg / L, the supernatant is passed into the clear water tank, and then the water in the clear water tank is passed into the sand and gravel processing system for reuse.

[0059] Example 3

[0060] This embodiment provides a method for treating wastewater produced by sand and gravel aggregate production in a hydropower station. The difference from Embodiment 1 is that the dosage ratios of the raw material components for preparing zeolite in this embodiment are different, specifically: the mass ratio of methyl orthosilicate, tetrabutylammonium hydroxide, dodecyltrimethylammonium chloride, and water is 1:0.08:0.3:150.

[0061] The following steps are used:

[0062] S1. The wastewater from the production of sand and gravel aggregates in the hydropower station is passed into a sedimentation tank, and flocculants are added into the sedimentation tank to perform sedimentation treatment on the wastewater;

[0063] The flocculant is a zeolite prepared from a silicon source, tetrabutylammonium hydroxide, dodecyltrimethylammonium chloride and water, and the mass ratio of methyl orthosilicate, tetrabutylammonium hydroxide, dodecyltrimethylammonium chloride and water is 1:0.08:0.3:150; the surface of the zeolite is coated with an adsorption film, and 40nm mesopores are formed on the surface of the zeolite; the adsorption film is prepared from quartz nanoparticles and polyethylene; the mass ratio of quartz nanoparticles to polyethylene is 1:0.5.

[0064] Wherein, the preparation method of flocculant is:

[0065] S1-1. Evenly mix methyl orthosilicate and water, and adjust the pH value to 10. Then, add tetrabutylammonium hydroxide and dodecyltrimethylammonium chloride dropwise, and stir to react to obtain silicate gel.

[0066] S1-2. Crystallize the silicate gel at a temperature of 80° C. for 95 hours, and then calcine the crystallized product at a temperature of 550° C. to obtain zeolite.

[0067] S1-3. Add quartz nanoparticles into water, stir and mix to prepare a suspension; the mass ratio of quartz nanoparticles to water is 1:110.

[0068] S1-4, adding polyethylene into the suspension and stirring to mix well to obtain a membrane liquid.

[0069] S1-5. The prepared membrane liquid is deposited on the zeolite by dip coating to form an adsorption film, thereby obtaining a zeolite flocculant with 40 nm mesopores on the surface.

[0070] S2. When the SS concentration in the supernatant of the sedimentation tank is less than 100 mg / L, the supernatant is passed into the clear water tank, and then the water in the clear water tank is passed into the sand and gravel processing system for reuse.

[0071] Example 4

[0072] This embodiment provides a method for treating wastewater from the production of sand and gravel aggregates in a hydropower station. The difference from Embodiment 1 is that the mesopores on the surface of the zeolite flocculant in this embodiment are 30 nm.

[0073] The following steps are used:

[0074] S1. The wastewater from the production of sand and gravel aggregates in the hydropower station is passed into a sedimentation tank, and flocculants are added into the sedimentation tank to perform sedimentation treatment on the wastewater;

[0075] The flocculant is a zeolite prepared from a silicon source, tetrabutylammonium hydroxide, dodecyltrimethylammonium chloride and water, and the mass ratio of methyl orthosilicate, tetrabutylammonium hydroxide, dodecyltrimethylammonium chloride and water is 1:0.05:0.25:100; the surface of the zeolite is coated with an adsorption film, and 30nm mesopores are formed on the surface of the zeolite; the adsorption film is prepared from quartz nanoparticles and polyethylene; the mass ratio of quartz nanoparticles to polyethylene is 1:0.5.

[0076] Wherein, the preparation method of flocculant is:

[0077] S1-1. Evenly mix methyl orthosilicate and water, and adjust the pH value to 10. Then, add tetrabutylammonium hydroxide and dodecyltrimethylammonium chloride dropwise, and stir to react to obtain silicate gel.

[0078] S1-2. Crystallize the silicate gel at a temperature of 80° C. for 95 hours, and then calcine the crystallized product at a temperature of 550° C. to obtain zeolite.

[0079] S1-3. Add quartz nanoparticles into water, stir and mix to prepare a suspension; the mass ratio of quartz nanoparticles to water is 1:110.

[0080] S1-4, adding polyethylene into the suspension and stirring to mix well to obtain a membrane liquid.

[0081] S1-5. The prepared membrane liquid is deposited on the zeolite by dip coating to form an adsorption film, thereby obtaining a zeolite flocculant with 40 nm mesopores on the surface.

[0082] S2. When the SS concentration in the supernatant of the sedimentation tank is less than 100 mg / L, the supernatant is passed into the clear water tank, and then the water in the clear water tank is passed into the sand and gravel processing system for reuse.

[0083] Example 5

[0084] This embodiment provides a method for treating wastewater from the production of sand and gravel aggregates in a hydropower station. The difference from Embodiment 1 is that the mesopores on the surface of the zeolite flocculant in this embodiment are 50 nm.

[0085] The following steps are used:

[0086] S1. The wastewater from the production of sand and gravel aggregates in the hydropower station is passed into a sedimentation tank, and flocculants are added into the sedimentation tank to perform sedimentation treatment on the wastewater;

[0087] The flocculant is a zeolite prepared from a silicon source, tetrabutylammonium hydroxide, dodecyltrimethylammonium chloride and water, and the mass ratio of methyl orthosilicate, tetrabutylammonium hydroxide, dodecyltrimethylammonium chloride and water is 1:0.05:0.25:100; the surface of the zeolite is coated with an adsorption film, and 50nm mesopores are formed on the surface of the zeolite; the adsorption film is prepared from quartz nanoparticles and polyethylene; the mass ratio of quartz nanoparticles to polyethylene is 1:0.5.

[0088] Wherein, the preparation method of flocculant is:

[0089] S1-1. Evenly mix methyl orthosilicate and water, and adjust the pH value to 10. Then, add tetrabutylammonium hydroxide and dodecyltrimethylammonium chloride dropwise, and stir to react to obtain silicate gel.

[0090] S1-2. Crystallize the silicate gel at a temperature of 80° C. for 95 hours, and then calcine the crystallized product at a temperature of 550° C. to obtain zeolite.

[0091] S1-3. Add quartz nanoparticles into water, stir and mix to prepare a suspension; the mass ratio of quartz nanoparticles to water is 1:110.

[0092] S1-4, adding polyethylene into the suspension and stirring to mix well to obtain a membrane liquid.

[0093] S1-5. The prepared membrane liquid is deposited on the zeolite by dip coating to form an adsorption film, thereby obtaining a zeolite flocculant with 40 nm mesopores on the surface.

[0094] S2. When the SS concentration in the supernatant of the sedimentation tank is less than 100 mg / L, the supernatant is passed into the clear water tank, and then the water in the clear water tank is passed into the sand and gravel processing system for reuse.

[0095] Example 6

[0096] This embodiment provides a method for treating wastewater from the production of sand and gravel aggregates in a hydropower station. The difference from Embodiment 1 is that in this embodiment, the mass ratio of quartz nanoparticles to polyethylene is 1:0.3.

[0097] The following steps are used:

[0098] S1. The wastewater from the production of sand and gravel aggregates in the hydropower station is passed into a sedimentation tank, and flocculants are added into the sedimentation tank to perform sedimentation treatment on the wastewater;

[0099] The flocculant is a zeolite prepared from a silicon source, tetrabutylammonium hydroxide, dodecyltrimethylammonium chloride and water, and the mass ratio of methyl orthosilicate, tetrabutylammonium hydroxide, dodecyltrimethylammonium chloride and water is 1:0.05:0.25:100; the surface of the zeolite is coated with an adsorption film, and 40nm mesopores are formed on the surface of the zeolite; the adsorption film is prepared from quartz nanoparticles and polyethylene; the mass ratio of quartz nanoparticles to polyethylene is 1:0.3.

[0100] Wherein, the preparation method of flocculant is:

[0101] S1-1. Evenly mix methyl orthosilicate and water, and adjust the pH value to 10. Then, add tetrabutylammonium hydroxide and dodecyltrimethylammonium chloride dropwise, and stir to react to obtain silicate gel.

[0102] S1-2. Crystallize the silicate gel at a temperature of 80° C. for 95 hours, and then calcine the crystallized product at a temperature of 550° C. to obtain zeolite.

[0103] S1-3. Add quartz nanoparticles into water, stir and mix to prepare a suspension; the mass ratio of quartz nanoparticles to water is 1:110.

[0104] S1-4, adding polyethylene into the suspension and stirring to mix well to obtain a membrane liquid.

[0105] S1-5. The prepared membrane liquid is deposited on the zeolite by dip coating to form an adsorption film, thereby obtaining a zeolite flocculant with 40 nm mesopores on the surface.

[0106] S2. When the SS concentration in the supernatant of the sedimentation tank is less than 100 mg / L, the supernatant is passed into the clear water tank, and then the water in the clear water tank is passed into the sand and gravel processing system for reuse.

[0107] Example 7

[0108] This embodiment provides a method for treating wastewater from the production of sand and gravel aggregates in a hydropower station. The difference from Embodiment 1 is that in this embodiment, the mass ratio of quartz nanoparticles to polyethylene is 1:0.6.

[0109] The following steps are used:

[0110] S1. The wastewater from the production of sand and gravel aggregates in the hydropower station is passed into a sedimentation tank, and flocculants are added into the sedimentation tank to perform sedimentation treatment on the wastewater;

[0111] The flocculant is a zeolite prepared from a silicon source, tetrabutylammonium hydroxide, dodecyltrimethylammonium chloride and water, and the mass ratio of methyl orthosilicate, tetrabutylammonium hydroxide, dodecyltrimethylammonium chloride and water is 1:0.05:0.25:100; the surface of the zeolite is coated with an adsorption film, and 40nm mesopores are formed on the surface of the zeolite; the adsorption film is prepared from quartz nanoparticles and polyethylene; the mass ratio of quartz nanoparticles to polyethylene is 1:0.6.

[0112] Wherein, the preparation method of flocculant is:

[0113] S1-1. Evenly mix methyl orthosilicate and water, and adjust the pH value to 10. Then, add tetrabutylammonium hydroxide and dodecyltrimethylammonium chloride dropwise, and stir to react to obtain silicate gel.

[0114] S1-2. Crystallize the silicate gel at a temperature of 80° C. for 95 hours, and then calcine the crystallized product at a temperature of 550° C. to obtain zeolite.

[0115] S1-3. Add quartz nanoparticles into water, stir and mix to prepare a suspension; the mass ratio of quartz nanoparticles to water is 1:110.

[0116] S1-4, adding polyethylene into the suspension and stirring to mix well to obtain a membrane liquid.

[0117] S1-5. The prepared membrane liquid is deposited on the zeolite by dip coating to form an adsorption film, thereby obtaining a zeolite flocculant with 40 nm mesopores on the surface.

[0118] S2. When the SS concentration in the supernatant of the sedimentation tank is less than 100 mg / L, the supernatant is passed into the clear water tank, and then the water in the clear water tank is passed into the sand and gravel processing system for reuse.

[0119] Comparative Example 1

[0120] This comparative example provides a method for treating wastewater from the production of sand and gravel aggregates in a hydropower station. Different from Example 1, no adsorption film is prepared on the surface of the zeolite in this comparative example.

[0121] The following steps are used:

[0122] S1. The wastewater from the production of sand and gravel aggregates in the hydropower station is passed into a sedimentation tank, and flocculants are added into the sedimentation tank to perform sedimentation treatment on the wastewater;

[0123] The flocculant is a zeolite prepared from a silicon source, tetrabutylammonium hydroxide, dodecyltrimethylammonium chloride and water, and the mass ratio of methyl orthosilicate, tetrabutylammonium hydroxide, dodecyltrimethylammonium chloride and water is 1:0.05:0.25:100; the surface of the zeolite is coated with an adsorption film, and 40nm mesopores are formed on the surface of the zeolite; the adsorption film is prepared from quartz nanoparticles and polyethylene; the mass ratio of quartz nanoparticles to polyethylene is 1:0.5.

[0124] Wherein, the preparation method of flocculant is:

[0125] S1-1. Evenly mix methyl orthosilicate and water, and adjust the pH value to 10. Then, add tetrabutylammonium hydroxide and dodecyltrimethylammonium chloride dropwise, and stir to react to obtain silicate gel.

[0126] S1-2, crystallizing the silicate gel at a temperature of 80°C for 95 hours, and then calcining the crystallized product at a temperature of 550°C to obtain a zeolite flocculant.

[0127] S2. When the SS concentration in the supernatant of the sedimentation tank is less than 100 mg / L, the supernatant is passed into the clear water tank, and then the water in the clear water tank is passed into the sand and gravel processing system for reuse.

[0128] Comparative Example 2

[0129] This comparative example provides a method for treating wastewater from the production of sand and gravel aggregates in a hydropower station. Different from Example 1, in this comparative example, no dodecyltrimethylammonium chloride is added to the raw materials for preparing zeolite, and tetrabutylammonium hydroxide is used instead.

[0130] The following steps are used:

[0131] S1. The wastewater from the production of sand and gravel aggregates in the hydropower station is passed into a sedimentation tank, and flocculants are added into the sedimentation tank to perform sedimentation treatment on the wastewater;

[0132] The flocculant is a zeolite prepared from a silicon source, tetrabutylammonium hydroxide, dodecyltrimethylammonium chloride and water, and the mass ratio of methyl orthosilicate, tetrabutylammonium hydroxide and water is 1:0.30:100; the surface of the zeolite is coated with an adsorption film, and 40nm mesopores are formed on the surface of the zeolite; the adsorption film is prepared from quartz nanoparticles and polyethylene; the mass ratio of quartz nanoparticles to polyethylene is 1:0.5.

[0133] Wherein, the preparation method of flocculant is:

[0134] S1-1. Evenly mix methyl orthosilicate and water, and adjust the pH value to 10. Then, add tetrabutylammonium hydroxide and dodecyltrimethylammonium chloride dropwise, and stir to react to obtain silicate gel.

[0135] S1-2. Crystallize the silicate gel at a temperature of 80° C. for 95 hours, and then calcine the crystallized product at a temperature of 550° C. to obtain zeolite.

[0136] S1-3. Add quartz nanoparticles into water, stir and mix to prepare a suspension; the mass ratio of quartz nanoparticles to water is 1:110.

[0137] S1-4, adding polyethylene into the suspension and stirring to mix well to obtain a membrane liquid.

[0138] S1-5. The prepared membrane liquid is deposited on the zeolite by dip coating to form an adsorption film, thereby obtaining a zeolite flocculant with 40 nm mesopores on the surface.

[0139] S2. When the SS concentration in the supernatant of the sedimentation tank is less than 100 mg / L, the supernatant is passed into the clear water tank, and then the water in the clear water tank is passed into the sand and gravel processing system for reuse.

[0140] All the above embodiments and comparative examples used wastewater from the same area, and the transmittance of the original wastewater and the transmittance of the supernatant after treatment were tested under the same conditions. The residual amount of flocculant in 100 ml of the supernatant was also tested. The test results are shown in the following table.

[0141] Experimental Case Transmittance of raw wastewater Transparency of supernatant Transmittance ratio Flocculant residue (g) Example 1 20% 90% 4.5 0.01 Example 2 20% 89% 4.45 0.015 Example 3 20% 90% 4.5 0.01 Example 4 20% 88% 4.4 0.018 Example 5 20% 90% 4.5 0.01 Example 6 20% 89% 4.45 0.015 Example 7 20% 90% 4.5 0.01 Comparative Example 1 20% 50% 2.5 1.0 Comparative Example 2 20% 40% 2.0 1.5

[0142] According to the above test results, the method in this application can be used to purify the sand and gravel aggregate wastewater of the hydropower station, especially after using the flocculant in this application, the treatment effect is better, the transmittance of the supernatant after treatment reaches 90%, which can be reused to achieve zero discharge of wastewater, and the flocculant can achieve complete sedimentation, with almost no residue in the wastewater. Compared with the comparative example, it can be seen that in the preparation components of the flocculant of this application, each raw material component is indispensable, and only under the raw material components and dosage ratio set in this application, the prepared flocculant can achieve a good sedimentation effect, and at the same time, the flocculant has less residue in the wastewater after treatment.

[0143] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for treating wastewater from sand and gravel aggregate production in a hydropower station, characterized in that: The following steps are involved: The wastewater from the production of sand and gravel aggregates in the hydropower station is passed into the sedimentation tank, and flocculants are added to the sedimentation tank to precipitate the wastewater; When the SS concentration in the supernatant of the sedimentation tank is less than 100 mg / L, the supernatant is passed into the clear water tank, and then the water in the clear water tank is passed into the sand and gravel processing system for reuse; The flocculant is a zeolite prepared from a silicon source, tetrabutylammonium hydroxide, dodecyltrimethylammonium chloride and water. The surface of the zeolite is coated with an adsorption film, and mesopores of 30nm to 50nm are formed on the surface of the zeolite. The adsorption film is prepared from quartz nanoparticles and a binder.

2. The method for treating wastewater from sand and gravel aggregate production in a hydropower station according to claim 1, characterized in that: The mass ratio of the silicon source, tetrabutylammonium hydroxide, dodecyltrimethylammonium chloride and water is 1: (0.02-0.08): (0.2-0.3): (50-150).

3. The method for treating wastewater from sand and gravel aggregate production in a hydropower station according to claim 2, characterized in that: The silicon source includes methyl orthosilicate, propyl orthosilicate or silica sol.

4. The method for treating wastewater from sand and gravel aggregate production in a hydropower station according to claim 1, characterized in that: The binder includes polyethylene or polypropylene.

5. The method for treating wastewater from sand and gravel aggregate production in a hydropower station according to claim 1, characterized in that: The mass ratio of the quartz nanoparticles to the binder is 1:(0.3-0.6).

6. The method for treating wastewater from sand and gravel aggregate production in a hydropower station according to claim 1, characterized in that: The preparation method of the zeolite comprises the following steps: The silicon source and water are mixed evenly, and the pH value is adjusted to 10-11, and then tetrabutylammonium hydroxide and dodecyltrimethylammonium chloride are added dropwise, and stirred to react to obtain a silicate gel; The silicate gel is crystallized, and then the crystallized product is calcined at a temperature of 530° C. to 560° C. to obtain zeolite.

7. The method for treating wastewater from sand and gravel aggregate production in a hydropower station according to claim 6, characterized in that: The crystallization temperature is 75° C. to 85° C., and the crystallization time is 90 h to 100 h.

8. The method for treating wastewater from sand and gravel aggregate production in a hydropower station according to claim 1, characterized in that: The preparation method of the adsorption film comprises the following steps: Adding quartz nanoparticles into water, stirring and mixing, and preparing a suspension; Adding a binder into the suspension and stirring to mix well to obtain a membrane liquid; The prepared membrane liquid is deposited on zeolite to form an adsorption membrane.

9. The method for treating wastewater from sand and gravel aggregate production in a hydropower station according to claim 8, characterized in that: The deposition method includes vacuum filtration, dip coating or suspension coating.

10. The method for treating wastewater from sand and gravel aggregate production in a hydropower station according to claim 8, characterized in that: The mass ratio of the quartz nanoparticles to water is 1:(100-120).

Citation Information

Patent Citations

  • Novel wastewater treatment adsorption material and preparation process thereof

    CN104722272A

  • Preparation method and applications of mordenite having mesopores and micropores

    CN106032281A

  • Method for reducing wastewater treatment and recycling cost of hydroelectric engineering gravel processing system

    CN112551731A

  • Ammonia-nitrogen wastewater treatment agent and preparation method thereof

    CN112591899A

  • Method of treating silicon-containing wastewater

    JP2013176721A